Identification of Arbuscular Mychorizae Fungi on Oil Palm in Bireuen, Aceh: Identification of Arbuscular Mychorizae Fungi on Oil Palm in Bireuen, Aceh - Zaitun Ritaqwin Rita; Mizan Maulana; Nazalia (SEAS (Sustainable Environment Agricultural Science), 2021)
Abstract Oil palm plantations in Aceh , especially in Bireuen, are generally planted on red-yellow podzolic soil types. Arbuscular mycorrhizal fungi (AMF) are fungi who are symbiotically associated with 97% of plant species. This study aims to identify the type and population of mycorrhizal spores from oil palm rhizosphere soil samples using culture trapping techniques (maize, sorghum, kudzu). This research was carried out in a greenhouse and Experimental Field, Faculty of Agriculture, Islamic National University of Indonesia, Bireuen, Aceh. Isolation, identification and observation of AMF colonization on plant roots was carried out at the Laboratory of Soil Biology, Faculty of Agriculture, Syiah Kuala University. The parameters included the number of arbuscular mycorrhizal fungi spores and the percentage of root colonization using the trapping culture method. The trapping culture method used 50 g of soil samples on oil palm rhizosphere which aged 5 months, 7 years, 9 years and 12 years. The results showed that the most dominant mycorrhizae found was the Glomus type. The mycorrhizae spores types found in the trapping culture were Glomus, Acaulospora and Gigaspora. The host plant that produced the most AMF spores was sorghum, while the highest AMF colonization of the three host plants was found in the roots of maize plants (78%) with very high criteria. Keywords: Oil palm, Culture trapping, AMF